Prevalência de leishmaniose visceral assintomática em doadores de sangue, em área endêmica para leishmaniose no Ceará - Monteiro, Daniela Cristina Sensato (2013)
Visceral Leishmaniasis (VL) is a public health problem worldwide. The urban transmission of Leishmania infantum (L. infantum) has been growing the prevalence of asymptomatic carriers of this parasite in large center. Occurrence of L. infantum transmission by blood transfusion has been reporting around the world, therefore it is important to evaluate the possibility of blood products as a potential risk for Leishmania transmission in endemic urban center. The aim of this study was to determine the prevalence of asymptomatic carriers of L. infantum among blood donors of Hemocenter of Ceará. It was used buffy coat of 438 blood donors, from May through November 2011. The positive samples for HIV, Hepatitis B and C, syphilis, HTLV, and Chagas’ disease were excluded from the study, resulting in 351 samples. The peripheral blood mononuclear cells (PBMC) and plasma were separated through Histopaque® centrifugation. For detection of the parasite, PBMC were used to perform the microculture in NNN medium and conventional PCR. Anti-leishmanial antibodies were detected through ELISA. The prevalence of L infantum in blood donors of asymptomatic carriers was high (16.5%), with 43 (12.2%) by serology and 15 (4.3%) by PCR. The DNA sequencing confirmed to be the genus Leishmania in 6 samples analyzed. Promastigote was not detected in micro cultures. The risk of LV transmission by blood transfusion exists. In Brazil, the blood banks do not performed routine screening for Leishmania, thus, the recommendation to include screening for Leishmania or the use of pathogen inactivation technology appears to be essential in endemic areas of VL.